PENGARUH NET PROFIT MARGIN (NPM) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PT. UNILEVER TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Vira Hardana Damanik; Miftahuddin Miftahuddin; Ahmad Prayudi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This research aims to determine the effect of Net Profit Margin and Debt to Equity Ratio on share price at PT. Unilever Tbk listed on the Indonesia stock Exchange (IDX). This type of research is causal asosiative which is to find out the cause and effect between the independent variabel (the variabel that affects) and the dependent variabel (the variabel affected). The populaton in this study is all financial statements at PT. Unilever Tbk listed on the Indonesia stock exchange from 2010 to 2018 per quarter . Based on the results of the F test, The Net Profit Margin and Debt to Equity Ratio has a significance value of 0,0000,05 and the Fcount shows a higher value than the Ftable that is 62,2863,31 which means that simultaneously Net Profit Margin and Debt to Equity Ratio have a positive influence and signifikant to stock prices. The value of the determinant coefficient (R2) is 0,806. So it can be concluded that 80,6% of the share price is influenced by other varibels not examined in this study.